Photochemical and electrochemical strategies in C–F bond activation and functionalization - Wang, Zhanghong; Sun, Yu; Liu-Yu, Shen; Wen-Chao, Yang; Meng, Fei; Li, Pinhua (Organic chemistry frontiers an international journal of organic chemistry, 2022)
The activation and functionalization of C–F bonds under mild conditions can serve as an important tool for organic syntheses including the modification of pharmaceuticals and agrochemicals and the synthesis of value-added chemicals. However, owing to their high energy and low activity, C–F bonds are difficult to activate. Thus, the direct activation of the C–F bond under mild or transition-metal-free conditions is a challenging research topic. Recently, photochemical or electrochemical C–F bond activation and functionalization has been evaluated as a scalable and sustainable approach that applies photons or electricity, respectively, to replace dangerous chemical oxidants or metal catalysts. To date, the achievements in this field have attracted great attention; however, reviews on photochemical or electrochemical C–F bond activation and functionalization are scarce. In this review, we summarize the recent significant developments in this rapidly growing area, mainly focusing on the reaction design and mechanisms.